Implementation of Dengue Hemorrahagic Fever (DHF) Case Reporting in Buleleng District - I Gede Peri Arista; Anak Agung Sagung Sawitri; I Made Suganda Yatra (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2022)
Background: Reporting cases of Dengue Hemorrhagic Fever (DHF) based on case definition the Ministry of Health of the Republic Indonesia is a strategy to increase the ability to predict positive cases. Our study aims to examine the implementation of case reporting so as to improve the predictive ability of positive cases.Methods: We conducted operational research at Kertha Usada General Hospital and Buleleng District Hospital. The sample is individuals diagnosed with DHF by a hospital having their address in Buleleng District and undergoing inpatient treatment at Kertha Usada General Hospital and Buleleng District Hospital in the first week of October 2021. We collected data through a review of medical record documents using a checklist.Result: We evaluated among 10 cases, 6 cases (60.0%) of whom were over 12 years old and 7 cases (70.0%) were men. Based on clinical indicators, among 10 cases, all cases (100%) actually had fever between 2-7 days, 5 cases (50%) really had headaches, 4 cases (40%) really had abdominal pain and 8 cases (80%) actually vomiting. Based on laboratory indicators, among all 10 cases (100%) there was a decrease in platelets <100,000 u/L and in 1 case (10%) there was an increase in hematocrit >52%.Conclusion : The positive predictive value obtained is 100% with very good positive predictive ability. Reporting cases based on the Ministry of Health of the Republic Indonesia case definition is expected to be carried out an ongoing basis because it can improve the ability to predict positive cases. Periodic training and technical guidance are required to equalize perceptions of case definitions so as to improve reporting quality.